Acetic acid improves drought acclimation in soybean: an integrative response of photosynthesis, osmoregulation, mineral uptake and antioxidant defense. Issue 2 (6th October 2020) - Rahman, Mezanur; Mostofa, Mohammad Golam; Keya, Sanjida Sultana; Rahman, Abiar; Das, Ashim Kumar; Islam, Robyul; Abdelrahman, Mostafa; Bhuiyan, Shahab Uddin; Naznin, Tahia; Ansary, Mesbah Uddin; Tran, Lam‐Son Phan
Abstract : Exposure to drought stress negatively affects plant productivity and consequently threatens global food security. As global climates change, identifying solutions to increase the resilience of plants to drought is increasingly important. Several chemical treatments have recently emerged as promising techniques for various individual and combined abiotic stresses. This study shows compelling evidence on how acetic acid application promotes drought acclimation responses in soybean by investigating several morphological, physiological and biochemical attributes. Foliar applications of acetic acid to drought‐exposed soybean resulted in improvements in root biomass, leaf area, photosynthetic rate and water use efficiency; leading to improved growth performance. Drought‐induced accumulation of reactive oxygen species, and the resultant increased levels of malondialdehyde and electrolyte leakage, were considerably reverted by acetic acid treatment. Acetic acid‐sprayed plants suffered less oxidative stress due to the enhancement of antioxidant defense mechanisms, as evidenced by the increased activities of superoxide dismutase, ascorbate peroxidase, catalase, glutathione peroxidase and glutathione S ‐transferase. Improved shoot relative water content was also linked to the increased levels of soluble sugars and free amino acids, indicating a better osmotic adjustment following acetic acid treatment in drought‐exposed plants. Acetic acid also increased stem/root, leaf/stem and leaf/root mineral ratios and improved overall mineral status in drought‐stressed plants. Taken together, our results demonstrated that acetic acid treatment enabled soybean plants to positively regulate photosynthetic ability, water balance, mineral homeostasis and antioxidant responses; thereby suggesting acetic acid as a cost‐effective and easily accessible chemical for the management of soybean growth and productivity in drought‐prone areas.